TRAINING ASSISTANCE IN MAKING NATA DE CITRULLUS LANATUS AS A HEALTHY DRINK FOR DIABETES MELLITUS - Shobirin; Megawati; Fiorenza An Nafisah; Jinani Firdausiah; Wilni Wahda Ulwiyati (Najah: Journal of Research and Community Service, 2023)
Most bevarages use chemical ingredients and much sythetic sweeteners that are consumed for a long period. To handle this situation, people have to start healthy lifestyle such as consuming nutritious food and drink. Therefore, a solution for this is to create a new healthy drink which is called nata de citrulus which has plenty of vitamins and minerals obtaining low calories, high fibers and high-water contents. This product consists of stevia leaves as natural sweeteners which has low sugar. The purpose of this research is to know the proportion of nutrition between nata decoco and nata de Citrullus lanatus, the effect of nata de Citrullus lanatus towards sugar ratio samples, and the prospect of nata de Citrullus lanatus drink. This research is analyzed by descriptive and linier regration statistics, showing nata de citrulus lanatus is better to consume for diabetes militus patients. The outcome of blood pressure tests, before and after consuming nata de citrulus lanatus, has changed. Male sample (aged 32 years), before consuming nata de citrulus, has blood pressure of 165/90 mmHg, and after consuming nata de citrulus lanatus throughout a week, there is changed in blood pressure at 130/80 mmHg. The linear regression analysis of variance test (paired T-test), the T count was at 2.64, the one-way T-table was at 1.73 and the two-way T-table was at 2.09. The results of hypothesis test proved that after giving nata de Citrullus lannatus to diabetes mellitus patients, it could reduce or stabilized the sugar levels of the samples. Moreover, the nata de Citrullus product has a cheaper selling price at 6000 IDR per bottle. So that, it can alleviate consumers in purchasing. In conclusion, Nata de Citrullus lanatus is able to reduce and stabilize the sugar level. In addition, it has the high amount in fibers, protein, and water level compared to others. Not only stabilizes the sugar level but it also declines the sugar level.